2012
DOI: 10.1007/s10637-012-9908-5
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog antagonists induce cell death in acute myeloid leukemia cells with the presence of lipopolysaccharides, tumor necrosis factor-α, or interferons

Abstract: Due to the development of drug resistance, the outcome for the majority of patients with acute myeloid leukemia (acute myelogenous leukemia; AML) remains poor. To prevent drug resistance and increase the therapeutic efficacy of treating AML, the development of new combinatory drug therapies is necessary. Sonic hedgehog (Shh) is expressed in AML biopsies and is essential for the drug resistance of cancer stem cells of AML. AML patients are frequently infected by bacteria and exposed to lipopolysaccharide (LPS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Consistent with the results of RNA-Seq, RT-PCR and western blot analyses also showed upregulated expression of GLI1 and p-AKT in the AML-RR patients. An in vitro study showed that inhibition of GLI1 depressed p-AKT activation and increased Ara-C sensitivity in leukemia cells, which is consistent with previous reports121527. These results indicated that these pathways might play important roles in the progression and drug resistance of leukemia.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results of RNA-Seq, RT-PCR and western blot analyses also showed upregulated expression of GLI1 and p-AKT in the AML-RR patients. An in vitro study showed that inhibition of GLI1 depressed p-AKT activation and increased Ara-C sensitivity in leukemia cells, which is consistent with previous reports121527. These results indicated that these pathways might play important roles in the progression and drug resistance of leukemia.…”
Section: Discussionsupporting
confidence: 91%
“…An additional mechanism linked to the resveratrol mediated inhibition of LSCs involves the interleukin‐6 (IL‐6) and sonic hedgehog (Shh) signaling axis. IL‐6 and Shh molecules are important to maintain the growth and expansion of LSCs . Recently, Su and coworkers have identified that the IL‐6 in plasma, Shh pre‐proteins, C‐ and N‐terminal Shh peptides in bone marrow and peripheral blood mononuclear cells in patients with AML are much higher than those in healthy individuals.…”
Section: Resveratrol and Pterostilbene Target Cscsmentioning
confidence: 99%
“…Other studies have shown that Hh signaling is essential for the survival and drug resistance of leukemia cells [22, 23]. Interestingly, a recent report has demonstrated that inhibition of the Hh pathway with LDE225 sensitizes AML cells to 5-azacytidine, and a clinical trial based on these results is ongoing [24].…”
Section: Introductionmentioning
confidence: 99%